PENGARUH WORK-LIFE BALANCE TERHADAP KEBAHAGIAAN YANG DIMEDIASI OLEH SELF-ESTEEM PADA KARYAWAN SEKTOR PERBANKAN KOTA BANDA ACEH - Faziatul Jannah; Irma Suryani (Departemen Manajemen, Universitas Syiah Kuala, 2020)
Abstract: This study aims to measure the effect of Work-life Balance to Happiness with Self-esteem as a mediating variable in the Banking Sector Employees in Banda Aceh City. The sample used in this study was employess of the banking sector, amouting to 141 respondens. Data collection equipment used in this study was a questionnaire. The sampling The sampling technique used is simple purposive sampling. Hierarchical Linear Modelling (HLM) was used as a method of analysis to determine the effect of all the variables involved. Based on the results of the HLM analysis indicated that Work-life Balance positively influence Happiness, Work-life Balance influence Self-esteem, Sels-esteem positively influence Happiness and Self-esteem partial mediate the relationship between Work-life Balance and Happiness.